Exploring the implementation of higher order thinking skills (HOTS) among islamic education teachers in Klang Valley - Siti Zalina binti Nor Monir (Kulliyyah of Education, International Islamic University Malaysia, 2019)
The Ministry of Education Malaysia has reviewed a curriculum that meets International standards by emphasizing the element of Higher Order Thinking Skills such as creative skills, innovation and problem solving to produce a balanced generation and master the skills of the 21st century. Higher Order Thinking Skills (HOTS) is the ability to apply knowledge, skills and values in reasoning and reflection to solve problems, make decisions, innovate and create. Students and teachers in Malaysia are given exposure to HOTS to be implemented in the teaching and learning session. Islamic Education Teachers (IET) also have to implement HOTS to make sure students nowadays can think out of the box. In order to realize this, IET have to truly understand the element of HOTS and how to implement it in the classroom. The study aims to examine the level of understanding HOTS among IET, the level of HOTS implementation in classrooms by IET, and to find out the relationship between the former and the latter. The study design was quantitative research, which involved 254 IET within Klang Valley. Descriptive statistics and correlations were used for data analysis. The findings of the study revealed that level of understanding, (Mean: 3.94, SD: .611) and implementation (Mean: 3.97, SD: .588) of HOTS among IET are in the high levels. There is also a significant relationship between IET understanding and their implementation of HOTS.